THE INFLUENCE OF DIGITAL LITERACY AND DIGITAL TRANSFORMATION ON THE RESILIENCE OF THE SHADOW EMBROIDERY INDUSTRY IN COASTAL DISTRICTS SOUTH WITH TECHNOLOGY DOPTION AS MEDIATION - Meli Putri Yana; Ma’ruf; Eri Besra (Halu Oleo University, 2024)
The transition to digitalization in the handicraft industry such as Shadow Embroidery in Pesisir Selatan Regency requires a series of innovations and transformations to survive and increase competitiveness. Therefore, mastery of digital literacy and the ability to carry out digital transformation are very important. This study aims to examine the effect of digital literacy and digital transformation on the resilience of the Shadow Embroidery industry in Pesisir Selatan Regency with the adoption of technology as a mediating variable. This study uses a quantitative approach with a sampling method using a saturated sampling technique, involving 87 respondents, all of whom are Shadow Embroidery industry players in Pesisir Selatan Regency. The data obtained were analyzed using the SEM-PLS 4.0 method to see the relationship between the variables studied. The results of this study indicate that all hypotheses have a positive influence.